Renewal of Implementing Regulations in Minimizing Control in Limited Liability Companies Outside of Acquisitions - Kartina Pakpahan; Willy Tanjaya; Wulan Me Ferina (Batulis Civil Law Review)
Introduction: The problem is that the definition of "control" of a company is not found explicitly in the Company Law, resulting in the emergence of practices of "control" of companies which are carried out not in accordance with the provisions as stipulated in the provisions of Article 1 point 11 and Article 125 paragraph (3) of the Company Law. When taking over company shares, it does not always result in a change in control of the company if the number of shares taken over does not exceed 50% of the company's shares. If the takeover of shares exceeds 50% of the company's shares, the party taking over a company will become the controller of the party being taken over.